Observed auroral ovals secular variation inferred from auroral boundary data - Zossi, Bruno Santiago (2021)
We analyze the auroral boundary corrected geomagnetic latitude provided by the Auroral Boundary Index (ABI) database to estimate long-term changes of core origin in the area enclosed by this boundary during 1983–2016. We design a four-step filtering process to minimize the solar contribution to the auroral boundary temporal variation for the northern and southern hemispheres. This process includes filtering geomagnetic and solar activity effects, removal of high-frequency signal, and additional removal of a ~20–30-year dominant solar periodicity. Comparison of our results with the secular change of auroral plus polar cap areas obtained using a simple model of the magnetosphere and a geomagnetic core field model reveals a decent agreement, with area increase/decrease in the southern/northern hemisphere respectively for both observations and model. This encouraging agreement provides observational evidence for the surprising recent decrease of the auroral zone area.